A Study on Digital Mode Classes During COVID -19 and Its Level of Satisfaction On Online Education Among School Students in Delhi NCR (International Journal of Innovative Research in Computer Science & Technology, 2021)
Around the world, online learning as well  as classes are becoming a bigger part of the educational  system. COVID-19 has caused a tremendous upheaval in  the educational system, not only in India but globally.  Virtual classes have replaced real classrooms at institutions  all around the world, including in India. While technology  makes things easier and more accessible, it may sometimes  be restrictive, especially in India, where many students do  not have access to the internet. As a result, there are issues  with attendance and interest in online sessions, making  online education channels difficult to adopt. Online  learning satisfaction is an important factor in supporting  effective educational processes. Despite the fact that online  learning is the sole option during the COVID-19 epidemic,  student and teacher satisfaction is critical to a successful  and effective learning experience. This study focus on the  Digital mode classes throughout COVID -19 and its level  of satisfaction on online Education among school students  in Delhi NCR region. The outcomes of the research show  that online courses and e-learning apps have a significant  impact on the everyday life of young people. Because  online classes are so popular, they should be seen as a  supplement and a great way to study throughout the  outbreak. The future aspects are, you may learn in a relaxed  setting with online education as well as online learning is  not only one of the most effective solutions for students,  but it is also more environmentally friendly.
Keywords: COVID-19; Education; E-learning; Online Classes; Students Satisfaction